2011
DOI: 10.1007/s11218-011-9153-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-schoolness in context: the tension between the youth project and the qualifications project

Abstract: In this ethnographic study conducted in two classrooms in Norway, grade nine (14-year-olds) in lower secondary school and the first year (16-year-olds) of upper secondary school, attention is drawn to how classroom culture is constituted through relationships between students. Through processes of power, dominance, hegemony and marginalisation, classroom culture forms the conditions for a learning environment, and has different opportunities, dilemmas and costs for the students. As classroom culture is negotia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
9
0
4
Order By: Relevance
“…These social processes coexist alongside the academic aspects of the classroom (Aasebø, ). Sometimes when locations and goals changed, often rapidly, we were able to observe actors moving between different participant roles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These social processes coexist alongside the academic aspects of the classroom (Aasebø, ). Sometimes when locations and goals changed, often rapidly, we were able to observe actors moving between different participant roles.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the social structure of the classroom has widened from focusing on the individual and how he or she interacts with his or her peers, to considering the social fabric and how it is transactionally modified by the individual's interactions with his or her dynamic environment (Stormshak, Bierman, McMahon, & Lengua, ). For instance, Aasebø (), in an ethnographic study, described classroom processes as involving power, dominance, hegemony, and marginalization. The purpose of the current ethnographic study was to further expand this focus into areas inaccessible through questionnaires or positivistic methodologies (Atkinson & Hammersley, ; Patton, ; Silverman, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Duncan and Owens (2011), in a study of the relationship between "bully" and "popular" in two English schools, found that popularity was highly related to attractiveness to boys in both schools, and also that popular girls tended to bully others. Regarding Norwegian studies of relevance, Aasebo (2011) showed that being high-achieving in upper secondary school did not qualify for popularity, while exhibiting heteronormative attractiveness and experimenting with alcohol and sex did. Heteronormativity (Butler, 1993) and the "male gaze" (Well, 2017) are implicit in the works of Duncan and Owens (2011) and Aasebo (2011). "…”
mentioning
confidence: 99%